Peran Visual Merchandising Dan Store Image Terhadap Peningkatan Customers' Purchase Intention - Kartika Anggraeni Sudiono Putri; Ikhsan Maksum; Amelindha Vania (Jurnal Ekonomi, 2021)
The purpose of this study is to examine the effect of visual merchandising to store image and purchase intention through the importance of visual merchandising factors such as front entrance product display, merchandising displays, store layout and organization, merchandising theme, signage/graphic, lighting and sound usage. This study also looked at the effects of store image on purchase intention. Ikea Alam Sutera Indonesia is used as a research object because, in the IKEA store, visual merchandising elements are designed in detail to create a unique shopping atmosphere for customers. The sample was 250 respondents drawn through non-probability sampling technique used purposive sampling with criteria of respondents had visited Ikea Alam Sutera. Data were analyzed using Structural Equation Modeling (SEM) with AMOS program version 24.0. The result shows that visual merchandising has positive influence on store image, whereby the greatest influence factors are lighting, merchandising theme and merchandising display. Nevertheless, visual merchandising did not have influence on purchase intention. Purchase intention known to be positively influenced by store image.